STRATEGI PEMERINTAH DESA DALAM PENGEMBANGAN OBJEK WISATA AIR TERJUN UMA ANYAR, DESA KEMENUH, KECAMATAN SUKAWATI, KABUPATEN GIANYAR - Paramitha Dewi, Ni Putu Jyoti; Supriliyani, Ni Wayan; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER; Vol 4 No 1 (2024): Vol.4 No.1, 2024)
The development of tourism potential in rural areas can make the region more advanced and prosperous than before. One of them is the village of Kemenuh which has the natural potential of Uma Anyar Falls which has natural beauty with various tourist attractions that can be done. The initial strategy was the acquisition of facilities and accessibilas, as well as the addition of other attractions. However, there are issues such as insufficient promotion, limited accessibility and lack of support facilities that require further development strategies. This research aims to find out the strategy implemented by the village government in the development of the tourist attractions of Uma Anyar Falls and recommend the appropriate strategy. Analysis of problems using indicators of strategy management theory according to Fred R. David (2011) with qualitative descriptive methods. Data is collected through interviews, observations, and documentation that are then analyzed using SWOT analysis techniques according to Freddy Rangkuti (2006). The findings show that the Kemenuh Village Government has undertaken strategic planning involving alignment with the vision and mission of the village and the long-term objectives of the tourist site, a thorough analysis of the internal and external environment, and the establishment of strategies for, and then implementation of complex strategies gradually, as well as conducting evaluation and monitoring. Recommendations that can be made include attractiveness development, socialization and training, resource optimization and innovation, as well as targeted promotion. Keywords : Strategy Management, SWOT, Village Government, Tourist Objects Development.